2005
DOI: 10.1029/2004jb003505
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical simulations of anisotropy of magnetic susceptibility on composite fabrics

Abstract: [1] The anisotropy of magnetic susceptibility (AMS) is an integral measure of the preferred orientation of all minerals present in a rock. When the AMS is carried by paramagnetic minerals alone, the principal directions of the susceptibility ellipsoid should reflect the crystallographic orientation of the minerals. The relationship between the AMS and deformation depends on several factors, which control the development of latticepreferred orientation (LPO) in a rock. A mathematical model is presented that sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Martín-Hernández & Ferré 2007;Oliva-Urcia et al 2009;Hirt & Almqvist 2012) and by comparing magnetic methods with numerical models based on independent analyses of the mineral fabric (e.g. Siegesmund et al 1995;Martín-Hernández et al 2005). As a ferromagnetic (sensu lato) fabric is usually affected by domain state, grain size and interaction between particles, it cannot be easily interpreted as a proxy for petrofabric intensity.…”
mentioning
confidence: 99%
“…Martín-Hernández & Ferré 2007;Oliva-Urcia et al 2009;Hirt & Almqvist 2012) and by comparing magnetic methods with numerical models based on independent analyses of the mineral fabric (e.g. Siegesmund et al 1995;Martín-Hernández et al 2005). As a ferromagnetic (sensu lato) fabric is usually affected by domain state, grain size and interaction between particles, it cannot be easily interpreted as a proxy for petrofabric intensity.…”
mentioning
confidence: 99%
“…5c). Similar attempts to model the carrier of paramagnetic subfabric by Martín-Hernández et al (2005) in the Luarca slates from Northern Spain were not always successful. They suggested that differences could arise if (1) the fabric is heterogeneous; (2) there is a false assumption about the mineral fraction responsible for the magnetic fabric; or (3) the intrinsic anisotropy of the single phases is incorrect.…”
Section: Paramagnetic Subfabricsmentioning
confidence: 99%
“…Errors may also arise in comparing texture and AMS if both measurements are not made on the same volume of material. Martín-Hernández et al (2005) provide an example for a case in which texture was determined by X-ray goniometry over an area of around 40 mm 2 and a penetration depth of B100 lm compared to AMS, which is based on a cylindrical core with a volume of 11.4 cm 3 . For this reason, a comparison is only valid if the deformation is homogeneous on the same order of size.…”
Section: Paramagnetic Subfabricsmentioning
confidence: 99%
“…Similarly, if AMS is controlled by phyllosilicates, it reflects the phyllosilicate crystallographic preferred orientation (CPO) [ Chadima et al ., ; Hirt et al ., ; Lüneburg et al ., ; Richter et al ., ; Siegesmund et al ., ]. Recent studies have been successful in modeling whole‐rock AMS from CPO data when several paramagnetic and diamagnetic minerals contribute, and in quantifying the contributions from each mineral [ Biedermann et al ., ; Martín‐Hernandez et al ., ; Schmidt et al ., ].…”
Section: Introductionmentioning
confidence: 99%